Design Patterns’ Model for Application Development in Object Oriented Languages (International Journal of Engineering and Computer Science, 2015)
Design patterns are one of the most efficient ways of application development. Many developers are still reluctant to the use of design patterns and development is carried out with not enough attention paid to the reusability and extensibility of the code. Patterns are not to be restricted in the building of integrated development environments and language libraries.Proposed work presents a model which use combination of multiple design patterns for application development in object oriented programming. The model suggested in this proposed work uses hierarchical abstraction of objects created using factory pattern. Façade pattern is also used which makes functional encapsulation possible. Proposed work also presents the scenarios in which use of patterns is likely to improve the code efficiency and reusability. Along with the factory pattern, singleton pattern may also to be used together in the proposed model for their respective benefits.